2016
DOI: 10.1038/jes.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to air pollutant PM2.5 and PM10 during pregnancy and risk of congenital heart defects

Abstract: Maternal exposure to ambient air pollution has increasingly been linked to congenital heart defects (CHDs). The objective of this study was to evaluate whether high levels of maternal exposure to PM2.5 and PM10 are related to increased risk of CHDs in Wuhan, China. We conducted a cohort study with a total of 105,988 live-born infants, stillbirths, and fetal deaths. The study included mothers living in the urban district of Wuhan during pregnancy over the 2-year period from 10 June 2011 to 9 June 2013. For each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
79
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 34 publications
4
79
2
Order By: Relevance
“…A large segment of population in the world, especially in developing countries, is exposed to fine particle matter (PM2.5) levels above the World Health Organization (WHO) annual air quality standards (>10 μg/m 3 ) . Epidemiologic studies have suggested an increased risk of congenital heart defects (CHD) in the offspring of mothers exposed to ambient air pollution and PM2.5 . Zebrafish is an ideal vertebrate animal model for investigating cardiac development, and we and others have shown that extractable organic matter (EOM) from PM2.5 has adverse effects on heart development in zebrafish embryos …”
Section: Introductionmentioning
confidence: 99%
“…A large segment of population in the world, especially in developing countries, is exposed to fine particle matter (PM2.5) levels above the World Health Organization (WHO) annual air quality standards (>10 μg/m 3 ) . Epidemiologic studies have suggested an increased risk of congenital heart defects (CHD) in the offspring of mothers exposed to ambient air pollution and PM2.5 . Zebrafish is an ideal vertebrate animal model for investigating cardiac development, and we and others have shown that extractable organic matter (EOM) from PM2.5 has adverse effects on heart development in zebrafish embryos …”
Section: Introductionmentioning
confidence: 99%
“…One of the more important factors that is of concern is the effect of air pollutants during maternal gestational period. Indeed, increased presence of PM is associated with numerous adverse birth outcomes, such as pre-term delivery (7), low birth weight (8), small gestational age of births (9), congenital heart defects (10), intrauterine growth restriction (11,12), stillbirth (13), and spontaneous abortion (14). Further, associated morbidities includes neurodevelopmental impairment leading to attention-deficit hyperactivity disorder (ADHD) and possible autism (15)(16)(17), neurological disorders such as impaired neurocognitive ability, nervous system sequelae (18), infant eczema (19).…”
Section: Introductionmentioning
confidence: 99%
“…One of the more important factors that is of concern is the effect of air pollutants during maternal gestational period. Indeed, increased presence of PM is associated with numerous adverse birth outcomes, such as pre-term delivery (7), low birth weight (8), small gestational age of births (9), congenital heart defects (10), intrauterine growth restriction (11,12), stillbirth (13), and spontaneous abortion (14). Further, associated morbidities includes neurodevelopmental impairment leading to attention-deficit hyperactivity disorder (ADHD) and possible autism (15)(16)(17), neurological disorders such as impaired neurocognitive ability, nervous system sequelae (18), infant eczema (19).…”
Section: Introductionmentioning
confidence: 99%